2006
DOI: 10.1081/lft-200056771
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oil Well Cementing Technology Using Natural Fibers

Abstract: In many industrial processes, the pipeline systems are lined with a protective layer of cement mortar. In petroleum wells, cement slurry is placed in a wellbore to be hardened into an impermeable mass that seals the annulus from fluid flow and protects the casing from corrosion for the life of the well. When uniform linings of neat cement fail in tension, one or more large cracks are formed and the pressurizing fluid or mud easily flows through the cracks. The necessity to check the damaging effect of plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Due to the brittleness of ordinary Portland cement, the cement sheath is prone to damage and destruction under external forces, affecting the quality of cementing and thus affecting the normal production of oil and gas wells. In severe cases, it can even lead to permanent shutdown of oil and gas wells, resulting in huge economic losses 6–10 . Therefore, it is necessary to study and prepare materials that can be used to improve the elasticity of cement stone, in order to enhance the ability of cement sheath to resist complex stress impacts, ultimately achieving the goal of improving cementing quality and ensuring the long‐term normal production of oil and gas wells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the brittleness of ordinary Portland cement, the cement sheath is prone to damage and destruction under external forces, affecting the quality of cementing and thus affecting the normal production of oil and gas wells. In severe cases, it can even lead to permanent shutdown of oil and gas wells, resulting in huge economic losses 6–10 . Therefore, it is necessary to study and prepare materials that can be used to improve the elasticity of cement stone, in order to enhance the ability of cement sheath to resist complex stress impacts, ultimately achieving the goal of improving cementing quality and ensuring the long‐term normal production of oil and gas wells.…”
Section: Introductionmentioning
confidence: 99%
“…Human hair (0.4% volume ratio) with length of greater than 2 cm was introduced to oil well cement type I. Plastic shrinkage cracking test was conducted and the result showed that human hair decreased the shrinkage cracking area by 92% [4].…”
Section: Introductionmentioning
confidence: 99%
“…HSH's strand has high tensile strength and friction coefficient. Due to this reason, human hair has been used for reinforcing clay based construction in rural areas of India, Bangladesh, Syria [1,24] and in European countries [25] with clay and other binders in plastering the house walls. Using human hair as fiber can reduce the shrinkage of more than 90% [26].…”
Section: Introductionmentioning
confidence: 99%